Mathematical operation and symbol notation
 Statements
H < J,
F < H,
I ≤ J = K
Conclusions
I. H > I
II. I ≥ F

View Hint View Answer Discuss in Forum
Given that,
H < J .....(i)
F < H .....(ii)
I ≤ J = K ......(iii)
On combining the statement (i), (ii) and (iii), we get
F < H < J = K ≥ I
Conclusions
I. H > I (false)
II. I ≥ F (false)Correct Option: D
Given that,
H < J ..............(i)
F < H ..............(ii)
I ≤ J = K ......(iii)
On combining the statement (i), (ii) and (iii), we get
F < H < J = K ≥ I
Conclusions
I. H > I (false)
II. I ≥ F(false)
So, it is clear that neither Conclusion i nor II follows the given statements.
 Statements
A > B,
B =H,
H > G
Conclusions
I. A > G
II. A > H

View Hint View Answer Discuss in Forum
Given that,
A > B .....(I)
B = H .....(ii)
H > G ...(iii)
On combining the statement (i), (ii) and (iii), we get
A > B = H > G
Conclusions
I. A > G (true)
II. A > H (true)Correct Option: E
Given that,
A > B .....(I)
B = H .....(ii)
H > G ...(iii)
On combining the statement (i), (ii) and (iii), we get
A > B = H > G
Conclusions
I. A > G (true)
II. A > H (true)
So, it is clear that both Conclusions I and II follow from the given statements.